Gambaran Resiliensi pada Ibu Nifas Primipara Suku Timor dalam Tradisi Neno Bo'ha - Tualaka, Yusi; Kristinawati, Wahyuni; Wahyuningrum, Enjang (Kuras Institute, 2025)
This study aims to explore the resilience in Timorese postpartum mothers who live the Neno Bo'ha tradition, which is a custom that requires mothers to undergo a postpartum recovery period in ume k'bubu (round house). This tradition is believed to provide long-term benefits for the health of mothers and babies, but on the other hand it also brings considerable physical and psychological challenges. This study uses a qualitative method with a phenomenological approach, which allows to explore the subjective experience of postpartum mothers in depth. The participants in this study are the primipara postpartum mothers of the Timorese tribe who are undergoing the Neno Bo'ha period in a round house. Data were collected through in-depth interviews and participatory observations to understand their adaptation process and resilience in facing the challenges of living this tradition. The results of the study showed that the postpartum mothers of the Timor tribe had a very good level of resilience. This can be seen from their ability to manage emotions, control impulses, maintain optimism, and take advantage of social support from family and society. Compliance with customs is a major factor in their resilience, although these traditions provide physical discomfort, such as heat, smoke, and pain arising from certain rituals. Support from family and community also played an important role in shaping their resilience during Neno Bo'ha's time.